2021
DOI: 10.3389/frvir.2021.730792
|View full text |Cite
|
Sign up to set email alerts
|

Teleportation in Virtual Reality; A Mini-Review

Abstract: Teleportation is a widely implemented virtual locomotion technique that allows users to navigate beyond the confines of available tracking space with a low possibility of inducing virtual reality (VR) sickness. This paper provides a comprehensive overview of prior research on teleportation. We report results from user studies that have evaluated teleportation in comparison to other locomotion methods and survey improved versions of teleportation. We identify a number of areas for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Upon further investigation, the literature review on teleportation techniques by Prithul et al [64] provided a detailed list of related techniques and studies, confirming this review's findings. Indeed, several VR teleportation techniques were enabled through physical interaction, as this review's findings also suggest.…”
Section: Motion-based Teleporting Typesupporting
confidence: 76%
“…Upon further investigation, the literature review on teleportation techniques by Prithul et al [64] provided a detailed list of related techniques and studies, confirming this review's findings. Indeed, several VR teleportation techniques were enabled through physical interaction, as this review's findings also suggest.…”
Section: Motion-based Teleporting Typesupporting
confidence: 76%
“…These strengths have been frequently echoed in the literature. Among the relevant empirical studies reviewed by Prithul et al (2021), nearly all studies confirmed a higher performance of teleportation compared to other artificial locomotion techniques. Accordingly, the research interest in this method has grown noticeably in recent years, as evidenced by two reviews of common navigation techniques (Boletsis, 2017), and (Boletsis and Chasanidou, 2022), conducted 5 years apart.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies have shown that navigation techniques can be improved by tailoring them to the specific use case at hand or by addressing relevant shortcomings (Krekhov et al, 2018;Caputo et al, 2019;Kraus et al, 2020;Adhikari et al, 2022;Tseng et al, 2022). Nevertheless, Prithul et al (2021) found that there are only a few publications that improve the teleportation by explicitly mitigating a known disadvantage of the technique. In this work, building upon the strengths of teleportation, we extend it with three interaction techniques dubbed Mini-Map, Portal Preview, and X-Ray Vision.…”
Section: Introductionmentioning
confidence: 99%
“…Several VR sickness mitigation strategies have already been developed, including the use of dynamic or foveated field-of-view (FOV) restriction ( Fernandes and Feiner, 2016 ; Adhanom et al, 2020 ; Yamamura et al, 2020 ) and vection blurring ( Budhiraja et al, 2017 ). In practice though, the bulk of locomotor VR experiences that are currently available rely primarily on the use of teleportation ( Al Zayer et al, 2020 ; Monteiro et al, 2021 ) which has been shown in a recent meta review ( Prithul et al, 2021 ) to result in significantly lower VR sickness incidence but at the cost of lower presence and potential spatial disorientation. The reason for the success of teleportation may be in part due to the lack of optic flow generated during use ( Prithul et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In practice though, the bulk of locomotor VR experiences that are currently available rely primarily on the use of teleportation ( Al Zayer et al, 2020 ; Monteiro et al, 2021 ) which has been shown in a recent meta review ( Prithul et al, 2021 ) to result in significantly lower VR sickness incidence but at the cost of lower presence and potential spatial disorientation. The reason for the success of teleportation may be in part due to the lack of optic flow generated during use ( Prithul et al, 2021 ). Optic flow can contribute to both vection ( Palmisano et al, 2011 ; Seno et al, 2018 ) and sensory conflict ( Bubka et al, 2007 ; Palmisano et al, 2011 ), which cause sickness in certain contexts ( Bubka et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%